2001
DOI: 10.1191/136216801678766877
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the effects of processing instruction and output-based instruction on the acquisition of the Italian future tense

Abstract: I also would like to thank all the students on the Italian courses at the University of Greenwich and Queen Mary for their forbearance and assistance during the data collection and the course arrangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
87
6
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(113 citation statements)
references
References 10 publications
18
87
6
2
Order By: Relevance
“…The results provided further empirical support for the findings of the previous studies by VanPatten and Wong (2004), VanPatten and Cadierno (1993) as well as Leeser and DeMil (2013). The findings of the current study were in contrast to the findings of (Benati, 2001(Benati, , 2005) and Collentine's (1998b).They found that both PI and traditional instruction groups performed similarly for the acquisition of complex Spanish grammar for both the production and interpretation tasks.…”
Section: Theory and Practice In Language Studiescontrasting
confidence: 57%
“…The results provided further empirical support for the findings of the previous studies by VanPatten and Wong (2004), VanPatten and Cadierno (1993) as well as Leeser and DeMil (2013). The findings of the current study were in contrast to the findings of (Benati, 2001(Benati, , 2005) and Collentine's (1998b).They found that both PI and traditional instruction groups performed similarly for the acquisition of complex Spanish grammar for both the production and interpretation tasks.…”
Section: Theory and Practice In Language Studiescontrasting
confidence: 57%
“…It has addressed the question of whether the effects of processing instruction endure, diminish or disappear over time. Overall the results of these studies showed that there are short-term durative effects for sentence-level tasks (VanPatten and Cadierno 1993;Cadierno 1995;Benati, 2001Benati, , 2004Farley, 2001Farley, , 2004Cheng 2002;Morgan-Short 2006;Lee and Benati 2007). Learners in processing instruction groups tend to maintain their improved performance (from the pre-test to the immediate post-test) from immediate post-tests to delayed post-tests up to one month from the original instructional exposure.…”
Section: Previous Research On Durative Effectsmentioning
confidence: 98%
“…VanPatten y Cadierno (1993) cuestionaron el valor de las prácticas de estructuras durante la instrucción gramatical, al entender que las actividades de output o de práctica de estructuras gramaticales resultaban insuficientes si no ayudaban a alterar las conductas de procesamiento de los aprendientes. Sin embargo, existen ya investigaciones con instrucción de procesamiento centrados en input y output enriquecido y comprensible (Collentine, 1998;Farley, 2004;Benati, 2001Benati, , 2005Llopis García, 2007, 2009 cuyos resultados mostraban que gracias al output estructurado los aprendientes fueron capaces de reforzar conexiones de forma y significado, ya que les hacía llevar a cabo prácticas llenas de significado que les permitían corroborar las hipótesis formuladas, e incorporar el conocimiento confirmado a su interlengua.…”
Section: Modelo De La Instrucción De Procesamiento Para El Artículo Eunclassified
“…Tanto el esquema presentado con los valores esenciales del artículo como el modelo de instrucción de procesamiento para la enseñanza/aprendizaje significativo del artículo han sido llevados al aula y sometidos a una minuciosa investigación empírica (Santiago Alonso, 2017) cuyos resultados acreditan la relevancia de la instrucción de procesamiento y el modelo operativo como modelo de instrucción válido para la enseñanza y el aprendizaje del artículo en español, colocándose en cuanto a los resultados obtenidos en la misma línea que investigaciones anteriores (VanPatten y Cadierno, 1993, Cadierno, 1995Collentine, 1998;Farley, 2004;Benati, 2001Benati, , 2005Llopis García, 2005, 2007, 2009) en cuanto a la eficacia de la instrucción de procesamiento como modelo de instrucción. Asimismo, dicho estudio empírico ha alcanzado las mismas conclusiones a las que el estudio de Llopis García (2005García ( , 2007García ( , 2009) llegaba en relación a la eficacia de la combinación de la instrucción de procesamiento con la gramática cognitiva para la enseñanza de formas lingüísticas de manera significativa.…”
Section: Conclusionesunclassified